2021
DOI: 10.1007/s11657-021-00956-z
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of zoledronic acid compared with sequential denosumab/alendronate for older osteoporotic women in Japan

Abstract: Summary Among hypothetical cohorts of older osteoporotic women without prior fragility fracture in Japan, we evaluated the cost-effectiveness of two treatment strategies using a simulation model. Annual intravenous zoledronic acid for 3 years was cost-saving compared with biannual subcutaneous denosumab for 3 years followed by weekly oral alendronate for 3 years. Purpose Osteoporosis constitutes a major medical and health e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…Since this review including publications up to December 31st 2019, other studies have suggested that sequential treatment may be cost effective [ 133 136 ]. Hiligsmann et al limited their population to women with severe osteoporosis in the US (50–80 years with BMD T-score ≤ -3.5 and without a history of prior fracture, or with a T-score of − 2.5 and − 3.5 with a history of ≥ 1 osteoporotic fracture); sequential abaloparatide (18 months) followed by alendronate (5yrs) was compared to generic alendronate monotherapy.…”
Section: Cost-effectiveness Of Sequential Treatmentsmentioning
confidence: 99%
“…Since this review including publications up to December 31st 2019, other studies have suggested that sequential treatment may be cost effective [ 133 136 ]. Hiligsmann et al limited their population to women with severe osteoporosis in the US (50–80 years with BMD T-score ≤ -3.5 and without a history of prior fracture, or with a T-score of − 2.5 and − 3.5 with a history of ≥ 1 osteoporotic fracture); sequential abaloparatide (18 months) followed by alendronate (5yrs) was compared to generic alendronate monotherapy.…”
Section: Cost-effectiveness Of Sequential Treatmentsmentioning
confidence: 99%
“…If a participant had a wrist or other bone fracture, corresponding one-time cost and disutility are assigned. Some more pharmacoeconomic evaluations regarding sequential therapy have been reported, which were based on the US or Japanese settings (40,48,49). These two studies in the United States demonstrated that abaloparatide followed by alendronate was dominant compared with sequential teriparatide/alendronate and was cost-effective compared with alendronate monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Kondo et al ( 57 ) suggested that sequential therapy using ZOL could suppress decreases in bone mineral density and increase of bone turnover marker if the period of denosumab administration was <3 years. Mori et al ( 58 ) used a simulation model to evaluate the effectiveness and cost of two treatment strategies. It was found that annual i.v.…”
Section: Discussionmentioning
confidence: 99%